CHARACTER VALUES IN NARRATIVE TEXTS OF ENGLISH TEXTBOOKS “BUKU GURU BAHASA INGGRIS” FOR SENIOR HIGH SCHOOL PUBLISHED BY THE MINISTRY OF EDUCATION AND CULTURE - Swastika, Sindy; Islam, Aang Fatihul (STKIP PGRI Jombang, 2020)
This research focuses to finding out the Character Values in Narrative Texts of English textbook “Buku Guru Bahasa Inggris” for Senior High School published by The Ministry of Education and Culture, to what extent character values was applied in the narrative texts, and how did teachers and students responses on the integration of character values in those English textbooks especially in narrative texts material and their implementation in teaching process and in daily life. In this design, the researcher has used qualitative and descriptive approach also the data were written description. In collecting the data the researcher used cluster random sampling and the researcher is the main instrument in collecting, identifying, analyzing and discussing the data. After doing the research, the research found character values found by the researcher in those narrative texts include hardwork, brave, helpful, kind-hearted, merciful, honesty, responsible, patient, spiritful, confidence, and loyalty. Then, there are four until six character values in each story. The results of this study also convinced that the teachers and students of Senior high school in Jombang has been implementing character education in teaching and learning activities, including in English subject and especially in narrative text material.